2016
DOI: 10.12688/f1000research.9932.1
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the CHEK2 gene in patients with cancer and their presence in the Latin American population

Abstract: Background:CHEK2(Checkpoint Kinase 2) encodes CHK2, a serine/threonine kinase involved in maintaining the G1/S and G2/M checkpoints and repair of double-strand DNA breaks via homologous recombination. Functions of CHK2 include the prevention of damaged cells from going through the cell cycle or proliferating and the maintenance of chromosomal stability.CHEK2mutations have been reported in a variety of cancers including glioblastoma, ovarian, prostate, colorectal, gastric, thyroid, and lung cancer in studies pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…An extensive literature review of Latin American studies on CHEK2 mutation by Guauque-Olarte et al examined 147 studies of various cancer samples of which 39 studies revealed mutations in CHEK2 [10]. The most common cancer present with a CHEK2 mutation was CCA with 8.6% [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive literature review of Latin American studies on CHEK2 mutation by Guauque-Olarte et al examined 147 studies of various cancer samples of which 39 studies revealed mutations in CHEK2 [10]. The most common cancer present with a CHEK2 mutation was CCA with 8.6% [10].…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature review of Latin American studies on CHEK2 mutation by Guauque-Olarte et al examined 147 studies of various cancer samples of which 39 studies revealed mutations in CHEK2 [10]. The most common cancer present with a CHEK2 mutation was CCA with 8.6% [10]. Moreover, the MUTYH mutation is associated with the autosomal recessive condition, MUTYH-associated polyposis (MAP), that has been previously linked to CCA [11,12].…”
Section: Discussionmentioning
confidence: 99%